The incorporation of literature in the English Language Programme for Engineering Students: learner interest and perception - Subarna Sivapalan,; Ganakumaran Subramaniam, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2008)
Literature has been an essential and popular component of language courses in the Malaysian English Second Language (ESL) context. Even so, the journey towards the inclusion of literature in language courses has been an evolving one, ensuing in many stages of change. As a result, the teaching and learning of literature was drawn back to a state of extinction from being an essential component of the language curriculum, only to resurge in a more fervent form. The introduction of the literature enhanced curriculum in the Malaysian ESL context has steered much discussion on the significance of teaching the subject as part of the English language syllabus in Malaysian primary, secondary and tertiary educational institutions. Although research on the teaching and learning of literature in Malaysian schools is rather abounding, not much research has been undertaken to investigate its effectiveness in Malaysian higher educational institutions. This paper discusses the findings of a study undertaken to investigate young adult learners’ perceptions on the inclusion of literature in the tertiary English language classroom. The focus of this paper is on perceptions, attitudes and the perceived needs of young adult technical learners towards the incorporation of literature in English programmes. The findings of the study, obtained via quantitative and qualitative approaches, provide insights that will help policy makers and educators in designing more appropriate programmes in relation to the incorporation of literature in ESL programmes for tertiary level young adult technical learners.